2012
DOI: 10.3109/15368378.2012.712587
|View full text |Cite
|
Sign up to set email alerts
|

Bidirectional frequency-dependent effect of extremely low-frequency electromagnetic field onE. coliK-12

Abstract: In the present work, the frequency-dependent effects of extremely low-frequency electromagnetic field (ELF EMF) on Escherichia coli K-12 growth have been studied. The frequency-dependent effects of ELF EMF have shown that it can either stimulate or inhibit the growth of microbes. However, the mechanism by which the ELF EMF affects the bacterial cells is not clear yet. It was suggested that the aqua medium can serve as a target through which the biological effect of ELF EMF on microbes may be realized. To check… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…Depending on the frequency non-ionizing radiation such as MV and extremely low frequency electromagnetic fields (ELF EMF) have stimulating or depressing effect on the growth and division of microorganisms (Martirosyan et al, , 2013b. However, the mechanism by which MV affect the bacteria cell is not clear yet (Martirosyan, 2012;Martirosyan et al, 2012Martirosyan et al, , 2013a.…”
Section: Introductionmentioning
confidence: 99%
“…Depending on the frequency non-ionizing radiation such as MV and extremely low frequency electromagnetic fields (ELF EMF) have stimulating or depressing effect on the growth and division of microorganisms (Martirosyan et al, , 2013b. However, the mechanism by which MV affect the bacteria cell is not clear yet (Martirosyan, 2012;Martirosyan et al, 2012Martirosyan et al, , 2013a.…”
Section: Introductionmentioning
confidence: 99%
“…By our previous experiment, performed on snail hearts, it has been shown that 4 Hz EMF-treated physiological solution (PS) modulates the growth and development of microbes and heart muscle contractility [3] [21].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have been established to verify the effects of ELF-EMF on cell functions (1,2). The effect of ELF-EMF has also been evaluated on bacteria in the studies (3)(4)(5). The results have been showed that ELF-EMF can negatively (6,7) or positively (8,9) effect on the living systems functions and bacteria antibiotic sensitivity, so some results are in contrast with each other.…”
Section: Introductionmentioning
confidence: 99%